Mapping Land Cover Changes Using Landsat TM: A Case Study of Yamal Ecosystems, Arctic Russia - Polina Lemenkova; Bruce C. Forbes; Timo Kumpula (Zenodo, 2012)
This paper details changes in land cover types and vegetation distribution in tundra landscapes during the past two decades. The main method of the work is classification of the Landsat TM scenes for land cover change detection. The new approach of the current work is application of GIS and remote sensing tools for Bovanenkovo region, since there is no previous remote sensing and GIS-based studies performed in the same area focusing research problem of land cover changes. The research area is geographically located on the Bovanenkovo region, the north-western part of Yamal Peninsula, West Siberia, Russia. The Yamal Peninsula is the world’s largest high-latitude wetland system covering in total 900,000 km² of peatlands, since lowland region creates ideal conditions for the development of wetlands, dense lake and river network (Kremenetski et al. 2003). The geomorphology of Yamal Peninsula is flat homogeneous land and low-lying plains with maximal elevations lower than 90 meters (Walker et al. 2009). Such environmental settings of Yamal facilitate seasonal flooding, active erosion processing, permafrost distribution and intensive local landslides formation.The dominating vegetation types on Yamal include different types of shrubs and willows, heath, grasses, moss, and lichens. Changes in land cover types in the Russian North are caused by various reasons. These include multiple ecological and social factors, such as permafrost degradation, reindeer grazing and gas-field development, as well as overall environmental changes, including climate (Walker et al. 2009). One of the factors causing changes in vegetation types in landslide formation. Thus, the early-stage vegetation, such as pioneering mosses or lichens usually follows recent landslide formation, while meadows and willow shrubs with high canopy points indicate later stages of vegetation regeneration after landslide activities. Therefore, distribution of the willow shrubs on bare slopes may indicate that these areas were landslide-affected in the ...